Media madness : public images of mental illness - Wahl, Otto F. (Rutgers University Press, 1995)
From Psycho, Silence of the Lambs, Kojak, and Melrose Place, from books, music, cartoons, advertising, and newspapers, we all derive our images of mental illness. These omnipresent media portrayals are at the least insensitive, inaccurate, and unfavorable and at the worst stigmatizing and pernicious. In this important book, Dr. Otto Wahl examines the prevalence, nature, and impact of such depictions, using numerous examples from film, television, and print media. He documents the remarkable frequency of these images and demonstrates how the media has stereotyped the mentally ill through exaggeration, misunderstanding, ridicule, and disrespect. Media Madness also shows the damaging consequences of such stereotypes - stigma, rejection, loss of self-esteem, reluctance to seek, accept, or reveal psychiatric treatment, discrimination, and restriction of opportunity. The forces that shape current images of mental illness are clarified, as are the efforts of organizations and individuals to combat such exploitation.